Tunisia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2010)
Tunisia's reliance on European countries for export earnings, tourism, remittances, and foreign direct investment inflows has remained high over the last decades. Remittances and tourism receipts have been broadly stable in percent of GDP, with somewhat more fluctuations in the latter caused in part by identifiable political events that harmed tourism in the region. Tunisia's annual growth rate appears to have become increasingly synchronized over time with the annual growth rate of its main European trading partners.